South Africa : Financial Sector Assessment Program-Technical Note on Cybersecurity Risk Supervision and Oversight. (IMF Staff Country Reports; Country Report, 2022)
Cybersecurity risk continues to grow both in complexity and severity and is a function of an increasingly open and interconnected cyber and financial ecosystem. The South African financial system has a long history of incorporating technology and as for many financial systems across the globe, digitalization has become a strategic priority. For risk management to keep pace with the dynamic nature of cyber threats and threat agents, systemically important financial institutions (SIFIs) have made substantial investments in cyber resilience programs (e.g., establishing cyber strategies, frameworks, and governance structures). Consistent with many jurisdictions, and partly a result of widespread remote working arrangements implemented in response to the global pandemic, cybersecurity threats to financial stability increased. However, high standards of risk management meant threats did not materialize into significant losses and/or disruptions.